DAYA SAING BANK SYARIAH DI SEBUAH NEGARA RELIGIUS: TEMUAN EMPIRIK DARI INDONESIA - Tastaftiyan Risfandy; Putri Permatasari Husa; Andi Asrihapsari (Jurnal Keuangan dan Perbankan, 2016)
This is the first study examining the market power of Islamic banks in Indonesia which using quarterly data. Specifically, this paper attempts to answer a question whether, in the high-religiosity country as Indonesia, Islamic banks have greatermarket power compared to its conventional counterparts. We construct Lerner’s index to measure banks market power by using data from 2009 to 2013. We found that even in a biggest Muslim country in the world, Islamic banks have lowest market power. The result suggests that central banks of Indonesia should consider an alternative methods to promote Islamic banks market power since the balance between those two types of banks may enhance country financial stability.